Revue bibliographique sur l’étude phytochimique et l’activité antioxydante des dattes Algériennes (Phoenix dactylifera L.) - Damene, Nour El Houda; Mecheri, Sara (My University, 2020)
Oxidative stress is said to be the source of various pathologies and the consequence of the excessive presence of free radicals in the body. The latter are molecules containing oxygen and are at the origin of the natural process of oxidation of cells. The synthetic antioxidants used are generally of carbochemical origin such as BHA (Butylhydroxyanisol), BHT (Butylhydroxytoluene). However, these substances affect the nervous system and increase the risk of allergy and certain cancers. Medicinal plants are important natural sources thanks to a wide variety of bioactive substances available to them. It is in this direction that our basic research has been oriented. Indeed, the objective of our work is the valuation of the date fruit (Phoenix dactylifera L.) by the data of previous studies. This is established by the qualitative and quantitative estimation of phytochemicals, as well as the evaluation of the antioxidant activity of this natural product. The results of previous research have highlighted the interesting content of dates in antioxidants (carotenoids, phenolic compounds, flavonols, flavonoids and condensed tannins). The two parts of dates (pulp and stone) have an interesting anti-free radical potential according to various analyzes carried out (DPPH, FRAP, CAT, ORAC, bleaching of β-carotene), this is comparable to that of synthetic antioxidants such as BHA (hydroxyanisolebutyl) and BHT (hydroxytoluenebutyl). Finally, it can be concluded from the present bibliographical research that the date constitutes a source of natural antioxidants (polyphenols) which can be used as additive products in therapy.
Keywords: dates; Phytochemistry; antioxidant activity; polyphenols